PENINGKATAN PRODUCTIVITAS DUMP BODY TRUCK MENGGUNAKAN PENDEKATAN LEAN MANUFACTURING STUDI KASUS DI PT. SANGGAR SARANA BAJA - TANGERANG - Yunianto Agung Nugroho (Journal Of Communication Education, 2016)
AbstractResulted in the increasing globalization of the world will be a world mining equipment needs to the needs of the growing impact of supporting the production of mining equipment. PT. Sanggar Sarana Baja is one of the companies supporting the production of mining equipment manufacturers are one of them is the Body Dump Truck. Body Dump Truck demand in 2013 increased from the previous year 2011 was only 120 units per year to 180 units per year. In the effort to deal with the demand, increased competition, cost pressures, the need to improve the performance of their manufacturing operations offer the Lean Manufacturing methods, tools, and heuristics to improve the effectiveness and efficiency in manufacturing. The purpose of this study is to provide the proposed increase in production capacity by identifying and balancing the work process that occurs in every work process production line must be equal or below tact time. The results of this study may indicate that the application of the production process of the proposed Dump Truck Body can be achieved from the monthly average of 10 units to 18 units. Jig fixture use a method very effective and efficient production processes, this is evidenced by the decrease cycle time. For each Sub-Assy previously had to be done with the two man power into one man power, and the lead time decreases. It's very good impact for companies to reduce operating costs of production as low as possible. Keywords: Produktivitas, Lean Manufacturing, Cycle Time, Man Power, Production.